Incongruence between Cardiorespiratory Fitness and Subjective Reports of Physical Activity in Multiple Sclerosis: A Focus on Sex Differences - Buragadda, Syamala; Snow, Nicholas J.; Gou, Alan P. C.; McShane, Joshua N.; Newell, Caitlin J.; Ploughman, Michelle (Multiple sclerosis international, 2024)
Purpose. The link between moderate- to vigorous-intensity physical activity (MVPA) and cardiorespiratory fitness in individuals with multiple sclerosis (MS) remains unclear. This study examined the relationship between self-reported MVPA and objectively assessed cardiorespiratory fitness, emphasizing sex differences. Methods. 107 adults with MS (77 females), aged (mean±standard deviation) 47.2±10.2 years, were recruited from a local MS clinic. Fitness was measured as maximal oxygen uptake (V̇O2max) during a graded maximal exercise test using a recumbent stepper. MVPA (24-hour recall) was estimated as the duration of activities≥3 MET (metabolic equivalent of task). MET-minutes were calculated by multiplying MET by duration. We explored sex differences in self-reported MVPA, cardiorespiratory fitness, and disability; examined sex differences in associations between these variables; and investigated whether MET-minutes of MVPA predicted V̇O2max in females and males. Results. Mean V̇O2max was 24.79 mL·kg-1·min-1, indicating poor cardiorespiratory fitness levels, despite high levels of self-reported MVPA (mean=412.5 MET-minutes). Fifty-three percent of males and 40% of females had V̇O2max levels below the 20th age- and sex-standardized population percentile, indicating poor cardiorespiratory fitness. There were statistically significant associations between MVPA and V̇O2max (Rho=0.27, p=.01), as well as disability and V̇O2max (Rho=−0.35, p=.02), in females but not males. A regression model using sex, age, body mass, disability, and MVPA to estimate V̇O2max was valid in predicting V̇O2max values that were statistically equivalent to those measured in the laboratory in females but not males. However, the inclusion of MVPA did not add to the predictive value of this equation. Conclusions. Despite reporting high levels of MVPA, people with MS had poor cardiorespiratory fitness. MVPA, fitness, and disability were associated in females only, indicating that sex differences should be considered in fitness appraisal. Self-reported MVPA did not predict fitness, suggesting 24-hour recall may not be representative of true activity or fitness levels in persons with MS. Future work should examine sex differences in associations between MVPA and fitness using objective measures such as accelerometry.